1999
DOI: 10.1007/s001670050165
|View full text |Cite
|
Sign up to set email alerts
|

Cyclops and cyclopoid formation after anterior cruciate ligament reconstruction: clinical and histomorphological differences

Abstract: Prospectively, 119 patients were pursued clinically and by follow-up-arthroscopy for the occurrence of a "cyclops syndrome" after ACL reconstruction with a patellar tendon autograft, augmented by LAD. Twenty-one patients showed nodular formations. Ten of these (group 1) developed early clinical evidence of a "cyclops syndrome" with a mean extension deficit of 19 degrees before follow-up-arthroscopy, on average 5.9 months after the index operation. The nodular formations found and excised during débridement had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
2
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 16 publications
1
55
2
4
Order By: Relevance
“…They found that in 2% of the patients a second surgery was needed in order to treat cyclops lesions, however, the prevalence of cyclops lesions in patients without severe loss of knee extension was not assessed. Previous studies based on second-look arthroscopy found an incidence of cyclops lesions between 14% and 21.5% [10, 15, 29]. Nevertheless, in these studies follow-up was only performed once, with inhomogeneous follow-up time points ranging from 8 and 36 months [10] and 14 to 70 months [29] after the ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that in 2% of the patients a second surgery was needed in order to treat cyclops lesions, however, the prevalence of cyclops lesions in patients without severe loss of knee extension was not assessed. Previous studies based on second-look arthroscopy found an incidence of cyclops lesions between 14% and 21.5% [10, 15, 29]. Nevertheless, in these studies follow-up was only performed once, with inhomogeneous follow-up time points ranging from 8 and 36 months [10] and 14 to 70 months [29] after the ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…The reason why cyclops lesions can cause loss of extension needs further investigation: a wide variety of tissue may contribute to the formation of cyclops lesions, including fibrous tissue, fibrocartilage, bone and fat. One possible explanation may be that “harder” variants of lesions could represent a mechanical obstacle at the end of the knee extension, whereas “softer” variants, such as cyclopoid scars, do not affect the range of motion, as shown by Muellner et al [15]. However, other studies did not find any cartilage or bone tissue in cyclops lesions causing limited knee extension [10, 14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclops lesions typically are small, with average sizes ranging from 10 to 15 mm (19). Two histologic types have been identified: true "hard" cyclops nodules and "soft" cyclopoid scars (20). True cyclops nodules contain osseous or cartilaginous tissue and are more prone to entrapment (cyclops syndrome).…”
Section: Arthrofibrosismentioning
confidence: 99%
“…Ein Abwarten bis zum Zeitpunkt der Metallentfernung ein halbes Jahr nach Rekonstruktion ist nicht sinnvoll. Für endgradige leichte Bewegungseinschränkungen waren vor allem die schon in der Literatur bekannten Zyklopstumoren, Notchimpingement und Verwachsungen verantwortlich[9,18]. Interessant ist hier, dass bei 9 Patienten keine Ursache für das endgradige Bewegungsdefizit im Rahmen der Kontrollarthroskopie gefunden werden konnte.…”
unclassified